2017
DOI: 10.1002/chem.201605891
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Gold Cyclic (Alkyl)(amino)carbene Complexes with Sub‐Microsecond Photoemissions: Structure and Substituent Effects on Redox and Luminescent Properties

Abstract: Table of Contents EntryCopper and gold complexes stabilized by cyclic (alkyl)(amino)carbene ligands ( R L)MX, where X = halide, pseudo-halide, amide or aryloxide represent a large class of photoluminescent materials, with emission lifetimes ranging from nanosecond to microsecond regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 69 publications
(110 reference statements)
7
135
0
1
Order By: Relevance
“…The exciton binding energy of copper (I) iodide was reported as 62 meV, which is larger than that of CsPbX 3 (≈18 meV) . This result implies that high PLQY and high exciton binding energy will be attained if a compound consisting of the spatially isolated [CuI] polyhedra is chosen . Kitada and Ishida reported a high PLQY of 73% for polymeric CuI complexes .…”
Section: Comparison Of Plqy Values Of the Blue Luminescence Of Halidementioning
confidence: 97%
“…The exciton binding energy of copper (I) iodide was reported as 62 meV, which is larger than that of CsPbX 3 (≈18 meV) . This result implies that high PLQY and high exciton binding energy will be attained if a compound consisting of the spatially isolated [CuI] polyhedra is chosen . Kitada and Ishida reported a high PLQY of 73% for polymeric CuI complexes .…”
Section: Comparison Of Plqy Values Of the Blue Luminescence Of Halidementioning
confidence: 97%
“…We have recently shown that cyclic (alkyl)(amino)carbene (CAAC) complexes of copper and gold show strong photoluminescence, with solid-state quantum yields of up to 96% [15,16]. We report here the syntheses, structures, reactivity and photoluminescence behavior of silver complexes with CAAC ligands with different degrees of steric hindrance, Me2 L, Et2 L, and Ad L (Chart I).…”
Section: Introductionmentioning
confidence: 97%
“…

A recent report introduced a new class of solution-processable TADF-type dopants based on carbene-metal-amide (CMA) materials. [5] Both the exchange energy and the oscillator strength in CMA compounds are calculated to depend on the dihedral angle between the carbene and amide ligands about the CmetalN axis, and on deformation of the CmetalN bond. [5] Both the exchange energy and the oscillator strength in CMA compounds are calculated to depend on the dihedral angle between the carbene and amide ligands about the CmetalN axis, and on deformation of the CmetalN bond.

…”
mentioning
confidence: 99%